Upaya Meningkatkan Kepercayaan Diri Siswa XE Melalui Bimbingan Klasikal PBL Berbasis Wordwall - madapur, Latifah (Jurnal Psikoedukasia, 2025)
This study was motivated by the low self-confidence of students in class XE at SMA Negeri 6 Semarang, as indicated by passive behavior, reluctance to ask questions, and feelings of inferiority in social interactions. The purpose of this research is to improve students' self-confidence through classical guidance services using the Problem Based Learning (PBL) method supported by Wordwall media. The hypothesis proposed is that classical guidance with the PBL method can enhance students' self-confidence. This research employed a Guidance and Counseling Action Research (PTBK) approach using the Kemmis and McTaggart model, carried out in two cycles. Data were collected through a self-confidence scale and analyzed descriptively. The results showed a significant increase in students’ self-confidence scores from pre-test to post-test. The application of PBL supported by Wordwall effectively created a participatory learning atmosphere and encouraged students to be more confident. These findings highlight the importance of innovative guidance strategies in supporting students' personal development in schools. Keywords: Self-Confidence, Classical Guidance, Problem Based Learning